Določanje parametrov nelinearnih modelov kaplanove turbine z diferenčno evolucijo - Kranjčič, Dalibor (visokošolska dela, 2014)
This doctoral dissertation describes development and identification of new models of double-regulated Kaplan turbines suitable for use in power system stability studies. Also it gives a detailed overview of the existing single and double regulated turbine models presented in scientific literature. The models are developed according to new concept called "virtual gate opening" (VOP). In this concept, the double-regulated turbine model is obtained as an extension of the nonlinear single-regulated turbine model through an approximation function that defines the relationship between the wicket gate opening and runner blades angle. The parameters of the approximation function are determined in the identification procedure using the VOP concept-based dynamic model, empirically determined differential evolution algorithm-based methods, field measurement data acquired during normal operating conditions and turbine characteristics data. Various types of surfaces used in the field of computer aided geometric design (CAGD) are applied for structure of the approximation function. The dissertation focuses on progressive development of differential evolution algorithm-based methods that are applied to determine different forms of the approximation functions, until an optimal form is attained that ensures the best possible agreement between the measured and calculated responses.
Keywords: aproksimacija funkcije; Disertacije; function appoximation; hidravlične turbine; hydraulic turbines; interpolacija; interpolation; Kaplanove turbine; Modeli; modeliranje elektroenergetskega sistema; optimizacija parametrov; parameter estimation; power system modeling; power system simulation; simulacije elektroenergetskega sistema